2017
DOI: 10.1111/ajpy.12121
|View full text |Cite
|
Sign up to set email alerts
|

Australian young adults’ tanning behaviour: The role of ideal skin tone and sociocultural norms

Abstract: Objective: Decreasing intentional tanning behaviour is a critical area of skin cancer prevention. Research evidence that tanning behaviour is significantly influenced by appearance motivations exists. The Tripartite Influence Model posits that internalisation of ideals about body image mediates the relationship between sociocultural norms and appearance-related behaviour and has been demonstrated primarily in the domain of weight. This study aimed to assess whether ideal skin tone (internalisation of a tanned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…While skin cancer incident rates do not differ significantly between genders (Skin Cancer Foundation, ), there was an overwhelming majority of female participants. Given that the current review identified only four studies of male participants, future research would benefit from including men in the study population, particularly as men also value a tanned appearance (Cancer Research UK, ; Day, Wilson, Hutchinson, & Roberts, ). As men may perceive tanning and appearance norms in different terms than women, such as reluctance to engage in practices regarded as feminine (Grogan, ), future appearance interventions with men may need to consider the role of masculinity.…”
Section: Discussionmentioning
confidence: 99%
“…While skin cancer incident rates do not differ significantly between genders (Skin Cancer Foundation, ), there was an overwhelming majority of female participants. Given that the current review identified only four studies of male participants, future research would benefit from including men in the study population, particularly as men also value a tanned appearance (Cancer Research UK, ; Day, Wilson, Hutchinson, & Roberts, ). As men may perceive tanning and appearance norms in different terms than women, such as reluctance to engage in practices regarded as feminine (Grogan, ), future appearance interventions with men may need to consider the role of masculinity.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the tanned body was seen as "healthy" and this led to the growth of use of indoor tanning using a sunbed. 79 However, the complexion and skin type of a large number of Australians who are the descendants of fair-skinned Europeans, is Type I on a scale of I-VI.…”
Section: Regulation and Prohibition Of Sunbedmentioning
confidence: 99%